Activity and Rotation in the Young Cluster h Per. Issue Volume 9:Issue S302(2013) (7th August 2014) - Argiroffi, C.; Caramazza, M.; Micela, G.; Moraux, E.; Bouvier, J.
Abstract: We study the rotation-activity relationship for low-mass members of the young cluster h Persei, a 13 Myr old cluster. h Per, thanks to its age, allows us to link the rotation-activity relation observed for main-sequence stars to the still unexplained activity levels of very young clusters. We constrained the activity levels of h Per members by analyzing a deep Chandra/ACIS-I observation pointed to the central field of h Per. We combined this X-ray catalog with the catalog of h Per members with measured rotational period, presented by Moraux et al. (2013). We obtained a final catalog of 202 h Per members with measured X-ray luminosity and rotational period. We investigate the rotation-activity relation of h Per members considering different mass ranges. We find that stars with 1.3 M⊙ > M 1.4 M⊙ show significant evidence of supersaturation for short periods. This phenomenon is instead not observed for lower mass stars.